(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Soil with low bearing and shear strength requires stabilization to improve its engineering properties and make it suitable for construction. In this study, rice husk and lime sludge are used for stabilization because they are locally available, reducing the amount of waste disposed of to the environment. The main objective of this study is to determine the optimum percentage rice husk and lime sludge for soil stabilization and to assess the effects of Rice husk ash and lime sludge percentage on the Atterberg limits. Apart from that also to assess the effects of Rice husk ash and lime sludge percentage on California Bearing Ratio and on maximum dry density and optimum moisture content. In this study, RHA and Lime sludge was added to the soil samples and various experiments were conducted on them to understand the effect the addition of these admixtures has on the soil. The RHA was added in percentages of 5,10, 15 and 20 %. The lime sludge was added in the percentages of 5,10,15 and 20 %. The test conducted on these samples were Liquid limit, plastic limit, standard proctor and CBR test. The results of these experiments showed that the addition of these admixtures caused the liquid limit of soil to decrease. The addition of RHA and Lime sludge caused the plastic limit to increase. The OMC increased as the percentage of RHA and lime sludge was increased in the samples. The OMC increased by 33 % for addition of 20 % RHA. The OMC increased by 37 % for addition of 20 % lime sludge. The MDD decreased as the percentage of RHA and lime sludge was increased in the samples. The MDD decreased by 23 % for addition of 20 % RHA. The MDD decreased by 25 % for addition of 20 % lime sludge. The CBR increased by 149 % for 20 % addition of RHA to the sample. The CBR increased by 137 % for 20 % addition of Lime Sludge to the sample. The samples with RHA showed greater improvement in strength compared with Lime Sludge.